ANALISIS KAUSALITAS ANTARA CAPITAL INFLOW DAN NILAI TUKAR RUPIAH DI INDONESIA PERIODE TAHUN 2000-2015 - Royka Basri; Yusbar Yusuf; Rosyetti ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine whether there is a significant interrelationship between capital inflow and the exchange rate in Indonesia in 2000-2015. This research uses secondary data in the period 2000-2015 sourced from Bank Indonesia and the Central Bureau of Statistics. In this study using quantitative analysis method using an econometric model, namely Restricted VAR (Vector Autoregression) or called Vector Error Correction Model (VECM). This study uses an analytical tool Eviews 9.0. The unit root test results indicate that the data for capital inflow and the exchange rate is not stationary at the current level, but data capital inflow and the exchange rate at the level of the first difference stationary. Cointegration test results showed that the relationship between capital inflows and the exchange rate in Indonesia has a long-run equilibrium relationship. Granger Causality Test results reveal that there is a direct relationship capital inflow affect the exchange rate, but the exchange rate does not affect the capital inflow, which means that only happens one-way relationship. Impluse Response Function Based on the results, it was found that the capital inflow had a negative effect on the exchange rate, as well as the exchange rate has a negative effect on capital inflow. While the results of variance decomposition shows that the role of capital inflow and significant rupiah.Keywords : Capital Inflow, The Rupiah, Granger Causality, VECM.